Representation of the Dynamics of ID Ego and Superego in the Film Screenplay Melawan Waktu - Gilang Sukma Ramadhan; Yusril (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to analyse the dynamics of Alif's personality structure in the Melawan Waktu scenario using Sigmund Freud's psychoanalytic approach. The focus of the study is on the imbalance between the id, ego, and superego after Alif loses his father, as well as its impact on family relationships and his life decisions. The method used is descriptive qualitative with a documentary study technique of the script. The data were analysed by identifying dialogues and scenes that represent psychological conflicts based on the concepts of the id, ego, and superego. The results show that the dominance of the id is evident through anger and impulsive behavior, while the superego is present in the form of guilt and moral pressure. An unstable ego gives rise to anxiety and interpersonal conflict. As the story progresses, a process of acceptance is evident, signifying a strengthening of ego function. This study confirms that dramatic conflict in the screenplay represents the psychological dynamics of humans in dealing with loss.